Medical specialist training: views from stakeholders - Md Azhar , Md Tahir; Abd. Manaf, Noor Hazilah (The Faculty of Medicine, International Islamic University Malaysia, 2015)
In Malaysia, medical specialisation training is mainly carried out by the public universities. A survey was carried out to explore the views of medical specialists in the country on issues such as structure of medical specialty training, availability of human resource, public/private sector competition, competency and apprenticeship, and its impact on assurance and quality of medical specialty training. Altogether 238 medical specialists from 30 hospitals and medical institutions in the country participated in the survey. Among the findings, competition for human resource between public and private sector and lack of uniformity on medical specialty training across universities in the country are among the issues found to be of concern. There is also a need to address governance issue which necessitates to clearly delineating what constitutes medical specialty and what constitutes a subspecialty so that an agreed uniformed nomenclature is exercised across all stakeholders. The respondents also strongly agreed on the need to ensure competence in medical specialist training.